Description of Tylencholaimus discus sp. n. (Nematoda, Dorylaimida, Tylencholaimidae) from Iran - Golhasan, Behrouz; Heydari, Ramin; Peña-Santiago, Reyes (Zootaxa, 2019)
A new species of the genus Tylencholaimus, collected in natural areas of Iran, is described and illustrated, including SEM observations. Tylencholaimus discus sp. n. is characterized by its 0.65–0.76 mm long body, lip region offset by weak constriction and 7–7.5 µm broad with a conspicuous perioral disc, odontostyle 6–7 µm long, odontophore 9–10.5 µm long and visibly flanged rather than knobbed, neck 230–259 µm long with anterior region weakly muscular and basal expansion 98–125 µm long or occupying 42–49% of total neck length, female genital system mono-prodelphic, posterior branch reduced to a uterine sac 2–20 µm long or much shorter (0.1–0.6 times) than body diameter but very occasionally consisting of uterus, sphincter and a small terminal mass all together measuring 35–40 µm long, V = 65–74, tail short and rounded (13–17 µm, c = 41–57, c’ = 0.6–0.8), and male unknown.